Beliefs about pain control and pain coping strategies in patients with gastrointestinal reflux disease - Marcinkowska-Bachlińska, Monika; Małecka-Panas, Ewa (Przewodnik Lekarza/Guide for GPs, 2006)
Background: The psychological aspect is very important in the pathogenesis, process and treatment of gastroesophageal reflux disease. Stress, pain control and pain strategies have an influence on perception of symptoms in patients with GERD Aim: Determination of beliefs about pain control and specification of pain coping strategies used by patients with reflux disease. Material and methods: We studied 50 patients with gastroesophageal reflux disease and 40 healthy subjects. Beliefs about pain control and pain coping strategies were assessed using BPCQ (the Beliefs about Pain Control Questionnaire) and CSQ (the Pain Coping Strategies Questionnaire) validated for the Polish population. Results: The results revealed significant differences in patients with GERD and control group in pain control and pain strategies. Conclusions: The data show that patients with GERD preferred external pain control and for that reason are likely to use failed pain coping strategies. This can be a cause of dissatisfaction of patients with GERD for treatment.